Juridical Review of Criminal Acts in the Ownership of Firearms and Ammunition - F M Ramadhan; S Rajab (Gerechtiheid Law Journal, 2020)
Criminalization is one aspect of criminal law that is often the subject of discussion in the community. There are times when the conviction is felt very light or very heavy when compared with the perpetrators. In fact, in criminal offenses, many things are taken into consideration, both in juridical and sociological aspects. The purpose of this study was to determine the application of criminal law for criminal acts of possession of firearms and ammunition in the decision No.102/Pid.Sus/2018/PN-Bau and to determine the legal considerations of judges in criminal acts of ownership of firearms and ammunition in the decision No.102 /Pid.Sus/2018/PN-Bau. This research is a qualitative normative law research that is more concerned with understanding the existing legal material rather than the quantity or amount of data. In normative legal research, researchers simply need to collect secondary legal materials and construct them in a series of research results. The nature of the research to be carried out is analytical descriptive. The results showed that the indictment was charged by the public prosecutor using a single indictment, namely Article 1 paragraph (1) of Law Number 12 of 1951 concerning firearms and explosives. Then the demands of the public prosecutor namely Dropping the criminal on Defendant Masrudin S Alias ​​Fajrin Bin La Isa with 7 (seven) months imprisonment were reduced as long as the defendant was in custody with an order that the defendant remain detained in Baubau Detention Center, and the panel of judges sentenced the criminal to the defendant Masrudin S Alias ​​Fajrin Bin La Isa, therefore was sentenced to five (5) months in prison. Judge's Legal Considerations in Criminal Acts of Ownership of Firearms and Ammunition in Decision Number 102/Pid.Sus/2018/PN-Bau. Based on the evidence, namely the witness' statement and the defendant's statement accompanied by evidence. the judge must consider all aspects including juridical, philosophical, and sociological aspects.